THE PANDEMIC SYNDROME: DEPRESSION AND ANXIETY IN MARGARET LAURENCE’S THE DIVINERS AND A JEST OF GOD (International Journal of Food and Nutritional Sciences, 2022)
This article advances the idea that an investigation of the impact of the pandemic is very much part and parcel of literary studies. Of recent times, the world has been a witness to COVID-19. When Margaret Laurence was writing her fiction, the impact of the infantile paralysis which ironically affected the adults too, left its impression on her writings. The novels namely The Diviners and A Jest of God, map out the precarious stigmatic experience of the characters. Even after they have grown up, the response to the pandemic is largely felt over the pages of the novel. The paper further explores how humans, inspite of their survival, carry the pandemic syndrome seeking ways to get rid of the stigma. The article briefly focusses on how Margaret Laurence encounters the pandemic impact on the characters as she records the experience in both the novels.